THE IMPACT OF VOCABULARY MASTERY AND READING INTEREST TOWARD THE STUDENTSâ COMPETENCE IN WRITING NARRATIVE ESSAY IN IV GRADES OF SD NEGERI 2 BOBOTSARI - Tama, Irviani Helma; Zainuddin, Enuh; Hawanti, Santhy (Universitas Muhammadiyah Purwokerto, 2015)
Abstract. The research was to know the impact of vocabulary mastery and reading interest towards the studentsâ competence in writing narrative essay in grade IV of SD Negeri 2 Bobotsari. The population of this research was all the students of SD Negeri 2 Bobotsari, and 48 samples was randomly chosen. The data were collected trough questionnaire and written test. The techniques in analyzing the data were normality test, homogeneity, linierity, correlation and regression analysis. The result of the reserch showed that were was a positive impact of vocabulary mistery on writing narrative essay competence. It could be seen from the result of the computation r = 0,31and tresult> ttable or 2,212 > 1,684 and with simple linier regression equation Å¶ = 55,70, 19 + 0,21 X1. Reading interest also had an impact on writting narrative essay competence with r = 0,26 and tresult> ttable or 1,89 > 1,684 and the obtained regression equation wasÅ¶ = 58,80 + 0,19 X2. When the vocabulary mastery and reading interest were done simultaneously, the result showed R = 0,15 and fresult> ftable or 5,08 > 3,21which meant it was significant with double linier regression equation which was obtained Å¶ =45,93+0,20X1+0,17X2.Â Keywords: writting competence, narrative essay, vocabulary mastery, andÂ reading interest.